Vplivi terenskih zvočnih snemalnih naprav na etnomuzikološke raziskave - Kunej, Drago (Traditiones (Ljubljana), 2001)
Ethnomusicological research has always been limited by the current level of technical development. It is interesting to watch to want extent ethnomusicology explores current technical possibilities when it employs audiorecording methods in the field, and how it adapt its research methods to the technology available at a given movement. Even though the current field recording technology is generally of a statisfactory quality, ethnomusicologists shoud use high-quality, professional recording equipment which provides the necessary technical quality of recordings; such material is then easier to process, to protect adaquately, and to store in archives. When purchasing technical equipment excessive economizing is not very prudent.It we take into consideration field research expenses and the processing of recorded material the expenses of researcher's work surpass those recording equipment and sound carriers which, in comparison, are low or even negligible
Keywords: etnomuzikologija; tehnična akustika; snemalne naprave